The effect of the COVID-19 pandemic on routine immunization services in Sierra Leone, 2021 - Kassim Kamara; Haurace Nyandemoh; Umaru Sesay; Adel Hussein Elduma; Godfrey Kayita; Gebrekrstos Negash Gebru (Journal of Interventional Epidemiology and Public Health)
Introduction: The COVID-19 pandemic resulted in movement and service restrictions during 2020 and 2021 that may have affected the essential immunization services in Sierra Leone. We analyzed the national routine immunization (RI) data to assess the effect of the COVID-19 pandemic in immunization coverage.